Oral microbial shift induced by probiotic Bacillus coagualans along with its clinical perspectives - Aysha Jebin A; Aparnna Suresh (Elsevier, 2023)
When used in adequate amounts, Probiotics are considered to beneficially affect host health in many respects. Bacillus coagulans, with its probiotic characteristics, has recently attracted the attention of many researchers and food manufacturers due to its high tolerance in extreme environments because of its spore-forming nature. Several beneficial effects of B. coagulans have been estimated as it exhibits properties of both the genera Bacillus as well as Lactobacillus. Recent literature has proven that B. coagulans has therapeutic effects on intestinal diseases including acute diarrhea, irritable bowel syndrome, antibiotic-related diarrhea, constipation, and colitis via modulation of the microbial composition, host immunity, and general metabolism. Due to the evidence supporting various probiotic effects of B. coagulans, the administration of many B. coagulans strains has been studied in the prevention and management of several oral diseases and conditions. The current review summarizes the probiotic characteristics and clinical, microbiological changes associated with the application of B. coagulans in oral health and diseases along with its future perspectives.